How Does Social Media Marketing Drive Skincare Purchases Through Brand Awareness and Image? - Afifah Wulandari; Herliani Rebecca Grace; Kurniawati Kurniawati (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2025)
Skincare products have become among the biggest cosmetic goods in the worldwide market. The rapid expansion of the cosmetic industry has made Indonesia as the fastest-growing market for cosmetics in Asia, can be seen from the emergence of various new skincare brands, both local and international, which results in increasingly intense market competition. One of the primary strategies employed to promote skincare products in Indonesia is Social Media Marketing. This research aims to examine the impact of Social Media Marketing on Purchase Intention, with Brand Awareness and Brand Image serving as mediators, in skincare products. A non-probability sampling method and purpose sampling, was applied in this research. Questionnaires were distributed to 287 respondents in order to collect data, consisting of social media users familiar with skincare products. Hypotheses were tested using Structural Equation Modeling with the assistance of AMOS24 software. The findings reveal that Social Media Marketing significantly affects Brand Awareness and Brand Image. Moreover, Purchase Intention and Social Media Marketing are influenced by Brand Image.